Specific high affinity interaction of Helicobacter pylori CagL with integrin αVβ6 promotes type IV secretion of CagA into human cells - Buß, Maren; Tegtmeyer, Nicole; Schnieder, Jennifer; Dong, Xianchi; Li, Jing; Springer, Timothy A.; Backert, Steffen; Niemann, Hartmut H. (Febs Journal, 2019)
CagL is an essential pilus surface component of the virulence-associated type IV secretion system (T4SS) employed by Helicobacter pylori to translocate the oncogenic effector protein CagA into human gastric epithelial cells. CagL contains an RGD motif and integrin α5β1 is widely accepted as its host cell receptor. Here, we show that CagL binds integrin αVβ6 with substantially higher affinity and that this interaction is functionally important. Cell surface expression of αVβ6 on various cell lines correlated perfectly with cell adhesion to immobilized CagL and with binding of soluble CagL to cells. We found no such correlation for α5β1. The purified αVβ6 ectodomain bound CagL with high affinity. This interaction was highly specific, as the affinity of CagL for other RGD-binding integrins was two to three orders of magnitude weaker. Mutation of either conserved leucine in the CagL RGDLXXL motif, a motif that generally confers specificity for integrin αVβ6 and αVβ8, lowered the affinity of CagL for αVβ6. Stable expression of αVβ6 in αVβ6-negative but α5β1-expressing human cells promoted two hallmarks of the functional H. pylori T4SS, namely translocation of CagA into host cells and induction of interleukin-8 secretion by host cells. These findings suggest that integrin αVβ6, although not essential for T4SS function, represents an important host cell receptor for CagL.
CRIS-Team Scopus Importer:2019-07-09
Keywords: CagL; Helicobacter pylori; integrin α; RGD motif; type IV secretion